Evolution of dwarf galaxies in a semi-analytic galaxy formation model. Issue Volume 14:Issue S344(2019) (August 2018) - Nagashima, Masahiro; Enoki, Motohiro; Ishiyama, Tomoaki; Kobayashi, Masakazu A. R.; Makiya, Ryu; Ogura, Kazuyuki; Okamoto, Takashi; Okoshi, Katsuya; Oogi, Taira; Shirakata, Hikari
Abstract: Dwarf galaxies provide us many important clues to understanding of galaxy formation. By using the current version of our own semi-analytic model of galaxy formation, in which cosmic structure forms and evolves based on the cold dark matter model of cosmology, we analyze dwarf galaxies. We find that the model well reproduces many properties such as magnitudes, sizes, and velocity dispersions of, especially, dwarf elliptical galaxies. We also find that the dynamical response of the gravitational potential well of dwarf galaxies to the supernova-induced gas removal plays a very important role to obtain large sizes and small velocity dispersions as observed.